Let f ( x ) be a 5th degree polynomial with f ( 1 ) = 1 , f ( 2 ) = 2 , f ( 3 ) = 3 , f ( 4 ) = 4 , f ( 5 ) = 5 , and f ( 6 ) = 3 6 . Find the value of f ( 1 0 ) − 1 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks for making my solution more clear
Log in to reply
You are welcome. You can such enclose your formula with "\ (" and "\ )" (no space between "\" and "(" and "\" and ")" to put the formula in LaTex You can place your mouse cursor over the formulas to see the LaTex codes or click the pull-down menu " ⋯ More" and select "Toggle LaTex" to see the LaTex codes.
Sir, can you explain how the general form of a fifth degree polynomial is like that? How would it be of a sixth degree polynomial and so on ?
Log in to reply
From the fact that f ( n ) = n for n = 1 , 2 , 3 , 4 , 5 . We note that f ( x ) = a ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) + x provides solution for x = n , because for x = 1 , 2 , 3 , 4 , 5 , a ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) = 0 , then f ( x ) = x . If you have 6th degree you will need another f ( x 1 ) = b . So that we can solve for the unknown a . In general to solution an n th degree polynomial of that form we need n + 1 conditions or equations.
The above 5th degree equation can be written as f(x)=k(x-1)(x-2)(x-3)(x-4)(x-5)+x
Where k is a constant.
Putting x=6, we get k= 4 1
Now, putting x=10, we get f(10)-10=3780
Problem Loading...
Note Loading...
Set Loading...
From the fact that f ( n ) = n for n = 1 , 2 , 3 , 4 , 5 , the 5th degree polynomial can be of the form
f ( x ) ⟹ f ( 6 ) ⟹ f ( x ) f ( 1 0 ) − 1 0 = a ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) + x = a ( 5 ) ( 4 ) ( 3 ) ( 2 ) ( 1 ) + 6 = 1 2 0 a + 6 = 3 6 = 4 1 ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) + x = 4 1 ( 9 ) ( 8 ) ( 7 ) ( 6 ) ( 5 ) + 1 0 − 1 0 = 3 7 8 0 where a is a constant. ⟹ a = 4 1